Does body scanning through visual imagery improve perception and function in patients after anterior cruciate ligament-reconstruction? An exploratory study. (2nd December 2022) - Amundsen, Olav; Starcevich, Cobie; Frisell, Even Johansen; Nordal, Tom; Williams, Sian; Mitchell, Tim; Beales, Darren
ABSTRACT: Introduction: Many people who have undergone Anterior Cruciate Ligament (ACL)-reconstruction do not return to their pre-injury level, with nonphysical factors recognized as barriers to recovery. Fear of movement has been linked to body schema distortions, and interventions directed at the body schema have shown potential to improve function. Objective: 1) Describe participants' ability to perform a visual imagery intervention (Body Scan); 2) investigate knee perception differences; 3) investigate if Body Scan led to improvements in perceptual differences; and 4) determine if some individuals improved in functional measures following the intervention. Methods: A single-arm intervention study was undertaken in people >12-month post ACL-reconstruction (n = 30). Body Scan was delivered using a standardized script developed for this study. Participants were assessed regarding their capacity to perform the Body Scan, perceptual differences between the knees and how perception changed following the intervention. Functional measures (vertical hop, triple hop, mSEBT, quadriceps strength, and hamstring strength) were taken. Results: 96.7% were able to perform a Body Scan, with 93.1% demonstrating a difference in perception between the knees. Of participants with perceptual differences, 92.5% demonstrated improvement in perception following the intervention. Ten participants had a clinically significant improvement in a functional measure following the intervention. Conclusion: Most participants could perform Body Scanning. The majority perceived perceptual differences between operated and non-operated knees, and reported more symmetric perception following the intervention. One-third of participants also showed improvements in a functional performance measure. Results suggest this intervention may be a helpful adjunct to rehabilitation post ACL-reconstruction, with further research warranted.